2014
DOI: 10.3892/mco.2014.408
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of 18F-fluorodeoxyglucose positron emission tomography - computed tomography compared to postoperative pathological findings for patients with non-small-cell lung cancer

Abstract: Abstract. This study was conducted to investigate the predictive value of 18 F-fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-FDG PET-CT) in patients with non-small-cell lung cancer (NSCLC), compared to that of postoperative pathological findings, for T and N staging and the associations of the metabolic parameters of the primary tumor with histological type and differentiation. The preoperative contrast-enhanced CT and 18 F-FDG PET-CT and postoperative pathological findings of 112 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…In this respect, Lee et al demonstrated only moderate FDG uptake especially in lymph node metastases of adenocarcinomas which was signi cantly less than that of lymph node metastases from squamous cell carcinomas [22]. However, Xue et al reported more favorable results for N-staging in 112 NSCLC patients undergoing FDG PET/CT and subsequent surgery [23]. They found a sensitivity of 92% and a speci city of 93%, which are comparable to our LCNEC data.…”
Section: Discussionsupporting
confidence: 82%
“…In this respect, Lee et al demonstrated only moderate FDG uptake especially in lymph node metastases of adenocarcinomas which was signi cantly less than that of lymph node metastases from squamous cell carcinomas [22]. However, Xue et al reported more favorable results for N-staging in 112 NSCLC patients undergoing FDG PET/CT and subsequent surgery [23]. They found a sensitivity of 92% and a speci city of 93%, which are comparable to our LCNEC data.…”
Section: Discussionsupporting
confidence: 82%
“…Generally, a lesion with higher FDG uptake has higher proliferation and reduced doubling time of tumor cells [24]. This can be seen in lung cancer patients, as primary lung cancer lesions showing higher SUV max generally have higher mass (MTV) [25,26]. However, the high metabolic activity in one primary site (SUV max ) and metastatic site (WB SUV max ) may not always be associated with a large metastatic burden.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that AC had a significantly lower metabolic activity than SCC and "other" histologies, consistent with prior reports. 19 This may reflect the inclusion of the more indolent forms of the AC subtype in our patient population, which are typically low in FDG uptake.…”
Section: Discussionmentioning
confidence: 97%